Identifikasi jenis dan ukuran bulir mineral magnetik pada lindi tempat pembuangan akhir (TPA) sampah Air Dingin Kota Padang menggunakan metode X-Ray Diffraction (XRD) - Robi Marcian (Department of Physics – Universitas Negeri Padang UNP, 2016)
A cities or urban areas having large population growth should be supported by the provision of advice and good infrastructure such as a waste management. Padang municipal waste management is done by the method of removal of garbage from disposal temporary to the final disposal that generate wastewater that leachate emanating from the garbage. Leachate is a liquid yellow, brown or black, and result from the decomposition process due to ingress of water, whether it is rain water or ground water, into a pile of garbage. If not managed properly, the surface of the water used by residents around the landfill is likely contaminated by pollutants called leachate (liquid waste / leachate). Mngetahui This study aims to determine the type and size of magnetic mineral grains in landfill leachate Air Dingin of Padang using X-Ray Difraction (XRD) Characteristing magnetic minerals is done using X-Ray Difraction (XRD) aims to determine the type of magnetic minerals and the size of the grains in the leachate. This study uses nine samples taken from 5 points leachate ponds, 2 points on the river, and 2 points of the gutter landfill Air Dingin of Padang. Samples of leachate pond, river, ditch and first extracted by using methanol bath soap that aims to separate the magnetic and non-magnetic minerals. Type of magnetic minerals can be determined by analyzing the peaks of the intensity of the XRD measurement results using Bragg law, while the grain size can be determined using the equation Scherrer. After analysing, the results showed that each sample contains the same type of mineral is magnetite (Fe3O4) which derived from the source - that is Anthopogenic. Magnetic mineral grain size of samples gutter Final Disposal (TPA) Air Dingin of Padang classified multi-domain (MD). Magnetite has the largest size is 193.25 μm with an average grain size of 63.90 lm